MAC‐v1: A new global aerosol climatology for climate studies. (4th October 2013) - Kinne, Stefan; O'Donnel, Declan; Stier, Philip; Kloster, Silvia; Zhang, Kai; Schmidt, Hauke; Rast, Sebastian; Giorgetta, Marco; Eck, Tom F.; Stevens, Bjorn
<x xml:space="preserve">Abstract</x> [1] The Max‐Planck‐Institute Aerosol Climatology version 1 (MAC‐v1) is introduced. It describes the optical properties of tropospheric aerosols on monthly timescales and with global coverage at a spatial resolution of 1° in latitude and longitude. By providing aerosol radiative properties for any wavelength of the solar (or shortwave) and of the terrestrial (or longwave) radiation spectrum, as needed in radiative transfer applications, this MAC‐v1 data set lends itself to simplified and computationally efficient representations of tropospheric aerosol in climate studies. Estimates of aerosol radiative properties are provided for both total and anthropogenic aerosol in annual time steps from preindustrial times (i.e., starting with year 1860) well into the future (until the year 2100). Central to the aerosol climatology is the merging of monthly statistics of aerosol optical properties for current (year 2000) conditions. Hereby locally sparse but trusted high‐quality data by ground‐based sun‐photometer networks are merged onto complete background maps defined by central data from global modeling with complex aerosol modules. This merging yields 0.13 for the global annual midvisible aerosol optical depth (AOD), with 0.07 attributed to aerosol sizes larger than 1 µm in diameter and 0.06 of attributed to aerosol sizes smaller than 1 µm in diameter. Hereby larger particles are less absorbing with a single scattering albedo (SSA) of 0.98 compared to 0.93 for smaller sizes. Simulation results of a global model are applied to prescribe the vertical distribution and to estimate anthropogenic contributions to the smaller size AOD as a function of time, with a 0.037 value for current conditions. In a demonstration application, the associated aerosol direct radiative effects are determined. For current conditions, total aerosol is estimated to reduce the combined shortwave and longwave net‐flux balance at the top of the atmosphere by about −1.6 W/m2 from which −0.5 W/m2 (with an uncertainty of ±0.2 W/m2) is attributed to anthropogenic activities. Based on past and projected aerosol emission data, the global anthropogenic direct aerosol impact (i.e., ToA cooling) is currently near the maximum and is projected to drop by 2100 to about −0.3 W/m2. The reported global averages are driven by considerable spatial and temporal variability. To better convey this diversity, regional and seasonal distributions of aerosol optical properties and their radiative effects are presented. On regional scales, the anthropogenic direct aerosol forcing can be an order of magnitude stronger than the global average and it can be of either sign. It is also shown that maximum anthropogenic impacts have shifted during the last 30 years from the U.S. and Europe to eastern and southern Asia.